THE INFLUENCE OF IMPLEMENTING OUTDOOR LEARNING METHODS ON LEARNING MOTIVATION OF SOCIAL STUDIES CLASS - Yusran Amir; Andi Parela (CV. Mitkom Indotama, 2023)
The research objectives were to (i) find out the description of the implementation of the outdoor learningmethod in social studies subjects at SMPS Maju Besitang (ii) find out the description of student learningmotivation in social studies subjects at SMPS Maju Besitang, (iii) find out the effect of implementingoutdoor learning methods on learning motivation students in social studies at SMPS Maju Besitang. Thistype of research is a true experiment with a pretest-posttest control group design. This research wasconducted at SMPS Maju Besitang. The population in this study were class VII students, totaling 48students. The samples used in this study were 43 students, 22 students of class VIIA and 21 students ofclass VIIB. The determination of the experimental group and the control group was carried out using asystematic random sampling technique. The research instrument was a learning design using datacollection techniques, namely teacher and student observation sheets and questionnaire instruments. Thedata obtained were analyzed by normality and homogeneity tests then followed by hypothesis testingusing the t-test. The research results show that; (i) The implementation of the outdoor learning methodin learning social studies for class VII students is carried out through 10 stages, where the results ofobservations of student and teacher activities are in the good category; (ii) social studies learningmotivation of class VII students after the application of the outdoor learning method in learning hasincreased learning outcomes, where learning outcomes are in the high category; (iii) There is an effectof implementing the outdoor learning method on social studies learning motivation for class VII studentsof SMPS Maju Besitang.